Cardiac Sympathetic Denervation in 6-OHDA-Treated Nonhuman Primates - Joers, Valerie (Public Library of Science, 2014)
Cardiac sympathetic neurodegeneration and dysautonomia affect patients with sporadic and familial Parkinson's disease (PD) and are currently proposed as prodromal signs of PD. We have recently developed a nonhuman primate model of cardiac dysautonomia by iv 6-hydroxydopamine (6-OHDA). Our in vivo findings included decreased cardiac uptake of a sympathetic radioligand and circulating catecholamines; here we report the postmortem characterization of the model. Ten adult rhesus monkeys (5–17 yrs old) were used in this study. Five animals received 6-OHDA (50 mg/kg iv) and five were age-matched controls. Three months post-neurotoxin the animals were euthanized; hearts and adrenal glands were processed for immunohistochemistry. Quantification of immunoreactivity (ir) of stainings was performed by an investigator blind to the treatment group using NIH ImageJ software (for cardiac bundles and adrenals, area above threshold and optical density) and MBF StereoInvestigator (for cardiac fibers, area fraction fractionator probe). Sympathetic cardiac nerve bundle analysis and fiber area density showed a significant reduction in global cardiac tyrosine hydroxylase-ir (TH; catecholaminergic marker) in 6-OHDA animals compared to controls. Quantification of protein gene protein 9.5 (pan-neuronal marker) positive cardiac fibers showed a significant deficit in 6-OHDA monkeys compared to controls and correlated with TH-ir fiber area. Semi-quantitative evaluation of human leukocyte antigen-ir (inflammatory marker) and nitrotyrosine-ir (oxidative stress marker) did not show significant changes 3 months post-neurotoxin. Cardiac nerve bundle α-synuclein-ir (presynaptic protein) was reduced (trend) in 6-OHDA treated monkeys; insoluble proteinase-K resistant α-synuclein (typical of PD pathology) was not observed. In the adrenal medulla, 6-OHDA monkeys had significantly reduced TH-ir and aminoacid decarboxylase-ir. Our results confirm that systemic 6-OHDA dosing to nonhuman primates induces cardiac sympathetic neurodegeneration and loss of catecholaminergic enzymes in the adrenal medulla, and suggests that this model can be used as a platform to evaluate disease-modifying strategies aiming to induce peripheral neuroprotection.